Nurses' blogs as part of a political process – Professional identity as a rhetorical resource for negotiating responsibility and blame. (September 2016) - Blomberg, Helena
Abstract: The working conditions of nurses in the Swedish healthcare system are often debated in the news media, where the various stakeholders׳ (nurses, union, politicians and healthcare managers) versions of events are laid out. By using social media, nurses can participate in the debate and in a political process by drawing on narrative elements as responses to politicians׳ and healthcare managers׳ neglect of the nurses׳ situations. This article reports on a study of 50 topic driven blogs written by nurses from 2013 to 2015 and published on the website of a union magazine for healthcare professionals. Departing from a discursive narrative approach, the aim of the study is to analyse how the nurses narrate their working conditions and what they convey. The study shows that the bloggers create a we-ness by constructing and displaying their professional identity, illustrating unfair working conditions, conveying criticism and negotiating responsibility and blame. Addressing other nurses, the bloggers presume that others in the profession experience similar things in their workplaces and thereby encourage them to take action and make the injustices known. In order to gain credibility for the reported events and the relations, rhetorical resources such as factual accounts, categories, pronouns and a media discourse are used. The media discourse that is (re)produced in the blogs and elsewhere may result in nurses being trapped in their way of talking about their working situation, normalising it and having difficulty finding solutions. Highlights: The approach reveals how professional identity is constructed and displayed. The use of rhetorical resources to gain credibility and accomplish actions. A displayed/constructed professional identity is important to mobilise other nurses.